An In-Depth Analysis of Multivitamin Purchasing Behavior Among Generation Z in Bandung - Kartika Nuradina; Dadan Abdul Aziz Mubarok; Detya Wiryany; Devyanthi Syarif; Nunung Ayu Sofiati; Prinska Damara Sastri; Benny Bernadus (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to describe consumer behavior in the decision-making process related to purchasing multivitamin products in Bandung City. Data were collected from 1,990 respondents through a survey and analyzed using descriptive statistical methods. The findings indicate that most consumers are 18–24 years old, married, and primarily work as students or private-sector employees, with a monthly income of less than IDR 2,000,000. The primary factor driving purchase decisions is health needs, followed by the product's perceived benefits and halal certification. The most influential sources of information include public media, such as social media and consumer reviews, as well as personal sources, including family and friends. Consumers in Bandung tend to delay their purchasing decisions without a specific timeframe. The main reason for repeat purchases is the consumer's experience of the product's tangible health benefits. These results provide valuable insights for multivitamin producers in designing effective marketing strategies grounded in consumer behavior.